The Challenges Women Face in Brazilian Jiu-Jitsu in the United States - Rachel Silverman; Anthony Dixon; Harriet Dixon (Journal of Athlete Development and Experience)
The purpose of this case study was to discover the challenges facing women participating in Brazilian jiu-jitsu in the United States, how they overcame these challenges, and why they continue to participate in Brazilian jiu-jitsu. Twenty-three female jiu-jitsu athletes participated in the study. Semi-structured interviews using open-ended questions were utilized. Analysis of challenges revealed three broader themes of Brazilian jiu-jitsu being male-dominated, gender norms and Brazilian jiu-jitsu being a contact sport. Women discussed how they coped with the challenges and the benefits they gain from participation. To increase the number of women involved in Brazilian jiu-jitsu, participants suggested more women’s-only classes and seminars, creating more awareness about female participation, being supportive of new women, trying multiple gyms to find the right fit, and persevering.